Penilaian Costumer Service Indeks Pada Cafe-Cafe Di Jalan Semeru Utama Jember - Toni Herlambang; Aditya Dimas Pratama (Institut Teknologi dan Sains Mandala, 2025)
Nowadays, the number of cafés in every region of Indonesia, including in Jember district, especially in the campus area is increasing. However, the existence or ability to survive of each café is very diverse. This type of research is quantitative and qualitative research in the form of numbers and qualitative data expressed in words. The results showed that the level of customer satisfaction was in the satisfied category with a Costumer Service Index (CSI) value of 71.04 percent. The results also show that there is a positive influence between service level and satisfaction. The higher the service level, the higher the level of satisfaction. In addition, the results also show that there is a negative influence between the level of expectations and the level of satisfaction. The higher the level of expectation, the lower the level of satisfaction.